Psikoedukasi Implementasi Pencegahan Bunuh Diri Remaja dalam Lingkup Keluarga - Dina Vebiana; Immanuela Andieny M. I. Sitanggang; Anisa Sulistya Nindita (Fakultas Psikologi Universitas Pancasila, 2022)
The importance of suicide problem in adolescent problem is becoming one of the cause of death in individuals aged 15 through 29, Therefore, a preventive measure is needed to prevent this problem, the focus of this community development program is family based intervention targeted to parents of 9th grade students in 1 Taman Public Middle School. Community development program was held through a workshop filled with materials and roleplay. Most of the participants have the interest in regards to the problem presented but have a lack of knowledge and skills in regards to suicide, this is presented through a less applicative answer during the roplay session. Therefore, it is necessary to have periodic training with the same topic.